Anterior referencing versus posterior referencing in total knee arthroplasty: a prospective observational study - Choudhary, Preetesh; Bahre, Skand; Tantuway, Vinay; Nagla, Ashok; Jain, Avinash; Gupta, Rishi (International Journal of Research in Orthopaedics, 2016)
Background: Femoral component rotation in total knee arthroplasty (TKA) is essential for patella-femoral tracking, ﬂexion gap balance and normal kinematic function of the knee. The two referencing techniques used for sizing and adjudging the femoral rotation are anterior referencing (AR) and posterior referencing (PR).The current study was designed so as to identify which referencing system determines the femoral rotation more accurately. Methods: This study involved 34 consecutive patients (22 females and 12 males) with 60 osteoarthritic knees (bilateral=26; unilateral =8) who satisﬁed the inclusion criteria. The trans-epicondylar axis, was taken as gold standard to adjudge the correct femoral rotation and was marked as E. The axis of rotation as per anterior instrumentation (A), and as per posterior instrumentation (P) were marked and compared as to which of the axis (A or P) was parallel to E. Results: A was always parallel to E, however P was parallel to E in 42 knees. In 18 knees (6 with valgoid deformity, 12 with hypertrophic osteoarthritis involving the medial femoral condyle), P and E tend to converge laterally, suggestive of excessive internal rotation. Conclusions: Anterior referencing determines femoral rotation more accurately than posterior referencing for knees with severe valgoid deformity or those with hypertrophic osteoarthritis involving the overgrowth of medial femoral condyle.